Podstawowe tendencje na europejskim rynku przewozów w transporcie lądowym - Brach, Jarosław (Basic Trends on European Transport Market in Land Transport, 2005)
For the last 15-20 years the road transport has been playing more and more important role in Europe. At the same time the railway transport has been losing its dominant in the past position. The main reason of that situation is the huge flexibility of road transport connected with the changes in the industry. But there are also many negative elements connected with that situation like for example congestion and growing of the pollution. So from one side the UE Authorities wants to revitalize the railway transport. From the second the road vehicles manufactures propose many solutions which can increase the efficiency of that mode of transport simultaneously cutting its negative effects of activity
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 39-50